Design, synthesis, and evaluation of bioactive molecules; Chiral polyvinylpyrrolidones supported Cu/Au nanoclusters catalyzed cyclization of 5-substituted nona-1,8-dien-5-ols - Zhang, Man (Kansas State University, 2017)
Small molecules are of great importance in drug discovery currently. The first three chapters discussed the design, synthesis and bio-evaluation of three different classes of small molecules and exploration of their biological targets. Triacsin C analogs were designed as long chain fatty acyl-CoA synthetase (ACSL) inhibitors for attenuating ischemia and reperfusion (I/R) injury. Oxadiazole derivatives were designed as T-type calcium channel inhibitors, which have potential application in the treatment of seizure and epilepsy. Tricyclic pyrone derivatives were reported as anti-Alzheimer lead compounds in previous research done by the Hua group. TP70 and CP2 were synthesized to explore their pharmacokinetics properties. Chapter 4 described chiral-substituted poly-N-vinylpyrrolidones (CSPVP) supported Cu/Au nanoclusters mediation of cyclization reaction of 5-substituted nona-1,8-dien-5-ols. A five-member cyclized lactone possessing a stereogenic tetrasubstituted carbon center was formed in a one-step Cu/Au nanoclusters-hydrogen peroxide oxidation reaction. This developed a novel and simple method to synthesize tetrasubstituted carbon stereogenic center. Drawbacks of the method in my initial study were low reaction yield and moderate enantioselectivity. The chemical yield and enantioselectivity have been significantly improved by introducing bulkier substitution in C3 and C4 positions of CSPVP according to the updates of ongoing research.
Keywords: Chiral-substituted polyvinylpyrrolidones (CSPVP)Bioactive small molecules